Management of third molars projected into the temporal fossa and infratemporal fossa: systematic literature review - Guégan Brendan; Casenave Théo; Lapeyrie Philippe; Benard Vincent (EDP Sciences, 2023)
Introduction: Projection of the maxillary third molar into the temporal or infra temporal fossa is a rare complication. There is no recommendation for the management of such complication. The aim of this work is to try establishing a removal protocol. Materials and methods: A systematic review of the literature was conducted using all cases reports of iatrogenic projection of the tooth into the temporal fossa or infratemporal fossa and how they were treated. The last search was conducted in July 2021. Results: 27 cases involving 28 teeth, published between 1986 and 2020 were included. Discussion: The intraoral approach seems to be preferred in the first instance for teeth in the infra temporal fossa and a cutaneous approach for teeth in the temporal fossa. This should be done within 3-6 weeks after projection to attempt removal. This allows the formation of a fibrous capsule and the downward migration of the tooth to facilitate removal. The use of complementary technological means can improve the chances of success. Conclusion: Resulting a flow chart, who is an aid to management of this type of situation, providing a clear idea of the approach to be taken.